Indocyanine green fluorescence-guided surgery in the emergency setting: the WSES international consensus position paper - Belinda De Simone; Fikri M. Abu-Zidan; Luigi Boni; Ana Maria Gonzalez Castillo; Elisa Cassinotti; Francesco Corradi; Francesco Di Maggio; Hajra Ashraf; Gian Luca Baiocchi; Antonio Tarasconi; Martina Bonafede; Hung Truong; et al. (World Journal of Emergency Surgery)
Abstract Background Decision-making in emergency settings is inherently complex, requiring surgeons to rapidly evaluate various clinical, diagnostic, and environmental factors. The primary objective is to assess a patient’s risk for adverse outcomes while balancing diagnoses, management strategies, and available resources. Recently, indocyanine green (ICG) fluorescence imaging has emerged as a valuable tool to enhance surgical vision, demonstrating proven benefits in elective surgeries. Aim This consensus paper provides evidence-based and expert opinion-based recommendations for the standardized use of ICG fluorescence imaging in emergency settings. Methods Using the PICO framework, the consensus coordinator identified key research areas, topics, and questions regarding the implementation of ICG fluorescence-guided surgery in emergencies. A systematic literature review was conducted, and evidence was evaluated using the GRADE criteria. A panel of expert surgeons reviewed and refined statements and recommendations through a Delphi consensus process, culminating in final approval. Results ICG fluorescence imaging, including angiography and cholangiography, improves intraoperative decision-making in emergency surgeries, potentially reducing procedure duration, complications, and hospital stays. Optimal use requires careful consideration of dosage and timing due to limited tissue penetration (5–10 mm) and variable performance in patients with significant inflammation, scarring, or obesity. ICG is contraindicated in patients with known allergies to iodine or iodine-based contrast agents. Successful implementation depends on appropriate training, availability of equipment, and careful patient selection. Conclusions Advanced technologies and intraoperative navigation techniques, such as ICG fluorescence-guided surgery, should be prioritized in emergency surgery to improve outcomes. This technology exemplifies precision surgery by enhancing minimally invasive approaches and providing superior real-time evaluation of bowel viability and biliary structures—areas traditionally reliant on the surgeon’s visual assessment. Its adoption in emergency settings requires proper training, equipment availability, and standardized protocols. Further research is needed to evaluate cost-effectiveness and expand its applications in urgent surgical procedures. Graphical abstract